QUALITY OF LIFE: A REVIEW OF THE COMPONENTS FOR CHRONIC KIDNEY DISEASE. - Zakirah Ahmad Nawi (Yayasan Pendidikan Medika Indonesia, 2023)
One of the best ways to evaluate a person's health quality is by measuring their Quality of Life (QoL). In assessing health, the QoL concept has exploded in popularity during the previous four decades. It has been used as the sole outcome in studies aimed at helping unhealthy patients improve their physical or emotional well-being. As a result, a specific evaluation method for health-related QoL is needed for this rapidly rising global population. This review aims to discuss components of QoL.